Evaluasi Penggunaan Website Puskesmas - Tri Wibowo, Kresno Ario; Prianggi, Herawati (Jurnal Bumigora Information Technology (BITe), 2023)
Background: Website technology greatly influences puskesmas services. Procurement of a website in order to meet user demands for easy, fast and efficient service availability. The website is provided to realize efforts to improve the quality of health services by integrating information systems from various subsystems. Objective: This research is related to the acceptance of the quality of the community health center website that is acceptable to users and looks for variables that influence users' interest in accessing the website page. Methods: This research was conducted using quantitative methods using the Unified Theory of Acceptance and Use of Technology (UTAUT). Results: There are four main constructs of website acceptance in the form of website performance, ease of using the website, environmental influence on using the website and condition of the website facilities. Conclusion: The level of acceptance of the website at the Puskesmas Banyuanyar with the Unified Theory of Acceptance and Use of Technology model has very high acceptance results. Variables that influence website user interest are website performance, ease of using the website, social influence and condition of facilities.